Eco-Friendly Environmental Management: The Synergy of Policy, Technology, and Public Behavior - Girly Farsyadiva Althaira Nurahim (Inovasi Pratama Internasional. Ltd, 2026)
Environmental degradation and increasing ecological risks indicate that the conventional development paradigm is no longer aligned with the principles of sustainability. This study examines eco-friendly environmental management as an integrative framework that emphasizes the synergy between public policy, the utilization of green technology, and the shaping of community behavior. The main issue examined is the gap between environmental legal norms and the effectiveness of their implementation in encouraging the adoption of green technology and pro-environmental behavior. This research employs a normative juridical method with statutory and conceptual approaches to analyze legal principles, environmental policies, and the implementation challenges of sustainable environmental management. The findings show that although the legal framework has provided a strong normative foundation, the effectiveness of environmental management remains hampered by policy fragmentation, limited institutional capacity, a lack of economic incentives, and low public environmental awareness. Green technology plays a strategic role in bridging environmental protection and economic development; however, its success is highly dependent on consistent policy support and changes in community behavior. This study affirms that eco-friendly environmental management is a transformative paradigm that requires a preventive approach, policy integration, technological strengthening, and public participation to achieve long-term environmental sustainability.